Functional Outcome, Revision Rates and Mortality after Primary Total Hip Replacement – A National Comparison of Nine Prosthesis Brands in England - Pennington, Mark (Public Library of Science, 2013)
BACKGROUND: The number of prosthesis brands used for hip replacement has increased rapidly, but there is little evidence on their effectiveness. We compared patient-reported outcomes, revision rates, and mortality for the three most frequently used brands within each prosthesis type: cemented (Exeter V40 Contemporary, Exeter V40 Duration and Exeter V40 Elite Plus Ogee), cementless (Corail Pinnacle, Accolade Trident, and Taperloc Exceed), and hybrid (Exeter V40 Trilogy, Exeter V40 Trilogy, and CPT Trilogy). METHODS AND FINDINGS: We used three national databases of patients who had hip replacements between 2008 and 2011 in the English NHS to compare functional outcome (Oxford Hip Score (OHS) ranging from 0 (worst) to 48 (best)) in 43,524 patients at six months. We analysed revisions and mortality in 187,201 patients. We used multiple regression to adjust for pre-operative differences. Prosthesis type had an impact on post-operative OHS and revision rates (both p<0.001). Patients with hybrid prostheses had the best functional outcome (mean OHS 39.4, 95%CI 39.1 to 39.7) and those with cemented prostheses the worst (37.7, 37.3 to 38.1). Patients with cemented prostheses had the lowest reported 5-year revision rates (1.3%, 1.2% to 1.4%) and those with cementless prostheses the highest (2.2%, 2.1% to 2.4%). Differences in mortality according to prosthesis type were small and not significant (p = 0.06). Functional outcome varied according to brand among cemented (p = 0.05, with Exeter V40 Duration having the best) and cementless prostheses (p = 0.01, with Corail Pinnacle having the best). Revision rates varied according to brand among hybrids (p = 0.05, with Exeter V40 Trident having the lowest). CONCLUSIONS: Functional outcomes were better with cementless cups and revision rates were lower with cemented stems, which underlies the good overall performance of hybrids. The hybrid Exeter V40 Trident seemed to produce the best overall results. This brand should be considered as a benchmark in randomised trials.